Multimedia Interaktif Pelajarpadu Berbasis Problem Based Learning Berbantuan Articulate Storyline bagi Guru dan Siswa Sekolah Dasar - Azizah; Nuraini; Pendit, Sinta Satria Dewi; Lapasere, Sisriawan; Rolly Bolalong, Roberto; Wahyuni, Sri; Rosnadi (Jurnal Pengabdian Kepada Masyarakat Patikala, 2025)
The background of this community service activity is the existence of problems at the partner school of SDN 6 Banawa, Donggala Regency, namely (1) data obtained that not all teachers have implemented the PBL model in learning. Other problems are (1) Teachers in implementing the PBL model still encounter errors, especially at the stage of student orientation to the problem. At this stage, some teachers directly present the material. They do not provide problems for students to solve in groups. and (2) the lack of teaching materials used to implement the independent curriculum. The purpose of this community service activity is to provide understanding and skills in implementing the PELAJARPADU Interactive Multimedia PBL model in learning. The implementation of community service uses an adult education approach which is usually called the Andragogy approach. Some techniques or methods that can be used in this community service are; group discussions, FGDs, brainstorming and demonstrations. Based on the dissemination activities, it can be concluded that (1) Teachers are enthusiastic about participating in the dissemination of research results on interactive multimedia (pelajarpadu) based on problem-based learning assisted by articulate storylines. (2) The implementation of interactive multimedia (pelajarpadu) based on problem-based learning assisted by articulate storylines received a positive response from participants. The teacher acknowledged that the results of the research could make it easier for teachers to implement the problem-based learning model in learning and make it easier to convey teaching materials to students in the classroom.